Decision Support System Budget Allocation Fund Village With AHP method (Analytic Hierarchy Process) In the village of beehive - Ilham Pramuja Nasution; Arjon Samuel Sitio (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
The budget allocation of a village fund is very important and take big effect to village progress Because the office to distribute the tax result for village development. But, that allocation is not accurately. Therefore there was design a system to support a decision a budget allocation of village funds by using an Analytical Hierarchy Process (AHP) method. This research done to the make-easy an office village in budgeting is the allocation of village funds. An method of Analytical Hierarchy Process (AHP) is one of a method known as important as the highest level. An AHP method is look for the best alternative